PEDAGOGIK YO‘NALISHLARDA TAHSIL OLUVCHI TALABALARDA SOG’LOMLASHTIRISH TEXNOLOGIYASI VA SALOMATLIKNI TARG‘IB QILUVCHI DUNYOQARASHNI SHAKLLANTIRISH - Mattiyev, I.B. (SCIENCE and SOCIETY, 2022)
This article describes the content of health technologies, the system of knowledge on the organization and conduct of healthy lifestyles, the formation of the fund of basic values of recreational physical culture, physical education in the field of health technologies, medicine, psychology and other fields. The importance of the system is emphasized of practical knowledge in various fields.
Keywords: worldview; education and upbringing; educational process; manifestation; perfection; new approach; flexibility; coordination; confidence; logical; practical knowledge system